Science & theatre : communicating science and technology with performing arts - Weitkamp, Emma; Almeida, Carla (Emerald Publishing Limited, 2022)
There has been a significant growth in initiatives involving theatre, drama and performance within a science communication context. Yet there is little scholarship exploring this phenomenon from a science communication perspective. Weitkamp and Almeida draw on their distinct experiences with theatre in the context of science communication to delve into initiatives created through dialogue between the arts and the sciences for the purpose of public engagement. Entering into the space where museums, universities and research centres operate, as well as the space of theatre practitioners, they explore the richness and plurality of this universe, combining theory and practice, as well as presenting context, knowledge gaps and new data. Acknowledging that the place of drama, theatre and performance within science communication is one which is uniquely influenced by local cultural practices, discourses and expectations, the authors take a global perspective. Firstly by analysing data from an international survey of practitioners and secondly by curating a collection of case studies on science-theatre projects undertaken around the world. The chapters illustrate the diversity of forms and content that comprises contemporary science-theatre in this context and characterise theatre produced within the scope of science communication, placing it more precisely in the broader context of science-theatre.